Cross-Language Modulation of Visual Attention Span: An Arabic-French-Spanish Comparison in Skilled Adult Readers - Awadh, Faris H. R.; Phénix, Thierry; Antzaka, Alexia; Lallier, Marie; Carreiras, Manuel; Valdois, Sylviane (Frontiers in Psychology, 2016)
In delineating the amount of orthographic information that can be processed in parallel during a single fixation, the visual attention (VA) span acts as a key component of the reading system. Previous studies focused on the contribution of VA span to normal and pathological reading in monolingual and bilingual children from different European languages, without direct cross-language comparison. In the current paper, we explored modulations of VA span abilities in three languages --French, Spanish and Arabic-- that differ in transparency, reading direction and writing systems. The participants were adult skilled readers who were native speakers of French, Spanish or Arabic. They were administered tasks of global and partial letter report, single letter identification and text reading. Their VA span abilities were assessed using tasks that require the processing of briefly presented 5 consonant strings (e.g., R S H F T). All five consonants had to be reported in global report but a single cued letter in partial report. Results showed that the VA span was reduced in Arabic readers as compared to French or Spanish readers who otherwise show a similar high performance in the two report tasks. The analysis of VA span response patterns in global report showed a left-right asymmetry in all three languages. A leftward letter advantage was found in French and Spanish but a rightward advantage in Arabic. The response patterns were symmetric in partial report, regardless of the language. Last, a significant relationship was found between visual attention span abilities and reading speed but only for French. The overall findings suggest that the size of VA span, the shape of VA span response patterns and the VA Span-reading relationship are modulated by language-specific features.